GIVE ME BACK MY BLACK DOLLS: DAMAS’ AFRICA AND ITS MUSEIFICATION, FROM POETRY TO MOVING PICTURES (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
This essay links Léon-Gontran Damas’ poetry to Matthias De Groof’s experimental film, Rendez-les moi, which is based on Damas’ poem “Limbé.” By offering an interpretation of “Limbé” in relation to the museification of African artifacts, the film frames the re-evaluation of Damas as artistic intervention. Kathleen Gyssels engages the way the visual experimentation tries to galvanize Damas’ artistic vision and focuses on the figure of Damas’ black dolls as a metaphor for gendered discrimination, thereby moving beyond classic antagonisms of Négritude.